Developed Photocatalytic Cotton Fabric with Agricultural By-Products Tea Saponins for Accelerating Aqueous Chromium(VI) Reductive Removal - Jiayu Gu; Yongchun Dong (Journal of Natural Fibers, 2024)
In order to achieve the goal of preparing functional textiles using tea saponin, in this work, carboxymethylated tea saponin (CTS) was used to modify cotton fabrics by an industrial rolling and baking process, and then functional textiles could be obtained after coordination with Fe3+, which could remove Cr species from water by photocatalytic reduction and adsorption processes. High CTS concentrations and higher treatment temperatures led to an increase in the carboxyl group content (QCOOH) and Fe content (QFe) of the obtained Fe-CTS-Cotton. The increase in the QFe value of the functional textiles favored the photocatalytic reduction of Cr(VI). Fe-CTS-Cotton with high QCOOH values showed excellent adsorption performance for the generated Cr(III) ions during the adsorption process. Therefore, the high photocatalytic reduction efficiency and strong Cr(III) ion trapping ability were the reasons for the recycling of Fe-CTS-cotton as a hybrid photocatalyst for enhanced removal of Cr(VI).